Evaluation of the impact of internal control environment on financial management of the Air Force of Zimbabwe (AFZ) - Chiduwa, Alex Munyaradzi (Midlands State University, 2018)
The Air Force of Zimbabwe (AFZ) like any other public sector companies is not spared from financial control irregularities in the form of fraud, unauthorised expenditure and misappropriation of funds. This has been evident during the audits by the Ministry of Defence internal audit and reports from the special investigations branch of the AFZ. Despite having an internal control system in place these practices continued to take place on an increasing scale. This has motivated the researcher to carry out a study on the impact of the internal control environment on the financial management of the AFZ. The research sought to establish the relationship between internal control environment and financial management. The appropriateness of the personnel involved in the financial management of the AFZ was to be determined as well as the challenges faced in ensuring an effective internal control environment. Relevant literature was reviewed in pursuance of the said objectives and a COSO model of the internal control environment was adopted for the purpose of this study. In line with the COSO model, the internal control environment was therefore broken down into the elements which include; Integrity and ethical values, management philosophy and operating style, organizational structure, assignment of authority and responsibility, human resource policies and practices and competence of personnel. After reviewing the existing literature it was concluded that the internal control environment is the foundation of the internal control system which in turn has a direct impact on financial management. This relationship therefore connected the internal control environment with the financial management. A descriptive approach was used during the study based on a sample. The sample was based on a judgemental sampling using the convenience sampling technique. Data was gathered through questionnaires and interviews. A triangulation of questionnaires and interviews ensured that data was verified and some objectives that were difficult to meet through the use of one method were achieved through the employment of the other method. Conclusions were drawn from data that was collected, presented and analysed. It was realised that an improvement in internal control environment was going to cause an improvement in the financial management of the AFZ. The research also revealed that most of the personnel in the finance section of the AFZ were under-qualified. Lack of funding came out as the major challenge in ensuring an effective internal control environment in the AFZ. It was recommended that the delegation of authority in the financial management be based on professional qualification rather than on military ranks.